Drug response is related to NR3C1 and FAAH polymorphism in Chinese pediatric epilepsy patients - Hongli Wang; Chu Li; Qian Li; Ning Li; Huiling Qin (Italian Journal of Pediatrics)
Abstract Background Childhood epilepsy is a common neurological syndrome with complex etiology and recurrent seizures. It seriously affects the growth and development of child patients. Methods NR3C1 rs41423247 and FAAH rs324420 polymorphisms were detected by the polymerase chain reaction in 105 pediatric epilepsy patients. Patients were divided into the good response group and the poor response group after anti-seizure medications (ASMs) treatment. According to the results of the liver function test (LFT), patients were divided into the no LFT disturbance group and the LFT disturbance group. Hardy–Weinberg balance was applied to analyze the population representation. The correlations were calculated by logistic regression analysis. Results NR3C1 rs41423247 genotype and allele frequencies differed significantly between good response and poor response groups, while FAAH rs324420 did not. The CG genotype and C allele of NR3C1 rs41423247 were associated with good drug response, and the association was also detected in the dominant model. In addition, polymorphisms in NR3C1 and FAAH were not associated with liver damage induced by epilepsy medication. Conclusion The polymorphism of NR3C1 rs41423247 might influence the drug response of epilepsy children.